The impact of statin use on short-term and long-term mortality in patients with heart failure - Zheng, Xiaoxue; Tan, Long; Zhang, Yu (Frontiers in Pharmacology, 2024)
Background:  Heart failure (HF) is a complex disorder that has an association with increased morbidity and mortality rates globally. The association of statin use with mortality rate in individuals with HF remains unclear. Objectives: To examine the association of statin use with the short-term and long-term all-cause mortality rate in critically ill individuals with HF. Methods: We performed a retrospective cohort analysis based on the Medical Information Mart for Intensive Care (MIMIC)-IV database. The critically ill people with HF were assigned to a statin group and a non-statin group according to whether they had been treated with statin or not during hospitalization. The Kaplan−Meier (KM) method and Cox proportional hazard models were adopted to explore the link between statin administration and the 30-day, 90-day, as well as 1-year mortality rates. To ensure the robustness of the findings, a 1:1 nearest propensity-score matching (PSM) was also performed. Results: The current research included 11,381 patients for the final analysis, with 7,561 in the statin group and 3,820 in the non-statin group. After multiple confounders were adjusted, we found that the Cox regression models revealed great beneficial effects of statin therapy on the 30-day, 90-day, as well as 1-year mortality rates among critically ill individuals with HF in the fully adjusted model. PSM also achieved consistent results. After PSM, the risk of mortality reduced by 23% for the 30-day mortality (HR=0.77, 95%CI: 0.68-0.88, p<0.001), 16% for the 90-day mortality rate (HR=0.84, 95%CI: 0.75-0.93, p=0.001), and 12% for the 1-year mortality rate (HR=0.88, 95%CI: 0.81-0.97, p=0.007). Patients treated with rosuvastatin had the greatest reduction in mortality rate. The 30-day, 90-day, and 1-year all-cause mortality rates were remarkably lower in patients who were treated with low-dose statins. Conclusions: Our study unveiled that statin use was related to decreased short-term and long-term all-cause mortality rates in critically ill individuals with HF. Rosuvastatin was associated with the greatest reduction of all-cause mortality rates. Low-dose statins can significantly reduce short-term and long-term mortality, while high-dose statins are not significantly correlated with mortality. However, the results are not conclusive and should be interpreted with caution.